Intraosseous inflammatory myofibroblastic tumor of the mandible with a novel ATIC-ALK fusion mutation: a case report. Issue 1 (December 2016) - Tateishi, Yoko; Okudela, Koji; Kawai, Shigeo; Suzuki, Takehisa; Umeda, Shigeaki; Matsumura, Mai; Kioi, Mitomu; Ohashi, Kenichi
Abstract Background Inflammatory myofibroblastic tumor (IMT) is a rare low-grade malignant neoplasm with a predilection for children and young adults, and typically arises in the lung, abdominopelvic region, and retroperitoneum. IMTs in the maxillofacial region are extreme rare. Approximately 50% of IMT harbor rearrangements of the anaplastic lymphoma kinase (ALK ) gene at 2p23 with various fusion partners. Case presentation We herein report a case of intraosseous IMT of the mandible with a novelATIC-ALK fusion. Tooth 43 did not erupt after the loss of tooth 83 in an 11-year-old girl with no previous history of trauma. Panoramic tomography showed a unilocular radiolucent lesion in the right anterior mandible resorbing the root of tooth 42 and the medial side of the root of tooth 44. Computed tomography revealed a well- circumscribed 3-cm osteolytic lesion of the right anterior mandible eroding the buccal cortical plate. The entire lesion was curetted out. A histopathological examination revealed the proliferation of plump spindle cells with a storiform architecture and lymphocytes scattered around spindle cells. The spindle cells showed diffuse cytoplasmic staining for ALK by immunohistochemistry. A fluorescencein situ hybridization analysis revealed the translocation of a part of theALK gene locus at chromosome 2p23. A rapid amplification of cDNA ends analysis confirmed the rearrangement ofALK and identifiedATIC as a partner of thisALK fusion mutant. Conclusion To the best of our knowledge, this is the first case of intraosseous IMT of the mandible with a novelATIC-ALK fusion. We also herein reviewed similar tumors reported in the literature.